Monitoring and Control System of Server Devices Based on IoT Using Sugeno Fuzzy - Achmad Syafriyal; Ilham Firman Ashari; Eko Dwi Nugroho (Department of Electrical Engineering, 2023)
Fire is a disaster or disaster caused by a fire, it can happen anywhere and anytime. Server is a very important asset for owners of companies or institutions that implement information technology. The importance of a server in an agency is because the server has applications and databases that store all important and valuable information for the company. A server must have security standards that protect the work of the devices in it and one of them is the temperature on the server device must always be in good condition. For this reason, in this study, a system that can perform supervision and control related to temperature, smoke and fire levels and can send notifications of the state of the server device is safe or not using the fuzzy logic of the Sugeno method. From the test results, the system can determine various server device conditions with accuracy reaching 100%. In fuzzy testing, the percentage of success is 100%. This shows that the results of testing the fuzzy method on the system are in accordance with the design that has been made. The system can determine the condition of the server device (Safe, Standby, Danger).